Investigating manufacturing small and medium-sized enterprises' immediate response and short-term recovery from flooding using an agent-based approach. (20th May 2019) - Alharbi, Meshal; Coates, Graham
The predominance and economic significance of small and medium-sized enterprises (SMEs) means widespread disruption can have severe financial consequences for a nation. This paper presents an agent-based approach enabling simulations to investigate manufacturing SMEs' immediate response to and short-term recovery from a flood event to evaluate the effectiveness of combinations of inundation precautions. Manufacturing SME agents exhibit pre- and post-flood behaviours gleaned from interviews with such businesses that have flood experience. Based on a flood event simulated for Sheffield in the UK, results show an individual SME with most precautions implemented in the lightly or moderately flooded area can return to 100% production approximately 7 days earlier than if the least precautions were employed. Further, considering the average short-term recovery of all SMEs with most precautions implemented in the lightly or moderately flooded area, 100% production can be achieved almost 20 days before manufacturers located in the severely flooded area.